Plantation land management, fires and haze in Southeast Asia - Helena Muhamad Varkkey (Environmental Management Society, Malaysia, 2011)
Forest fires and its resulting haze has been a recurring transboundary environmental problem in Southeast Asia. This research paper shows the strong correlation between the opening of plantation land in Indonesia and Malaysia and fires that cause haze. It argues that commercial plantations contribute significantly more to open burning fires than small-scale slash-and-burn farmers. It shows that economic motivation and governmental encouragement has motivated commercial plantations, especially for oil palm, to open land on fire-prone peatland and old cropland, producing smoke that often travels across borders. This has contributed to and exacerbated the transboundary haze problem in the region. This paper discusses two types of land use change often employed in Indonesia, and to a lesser extent Malaysia, for conversion into oil palm plantations, and how they are linked with increase in fires: conversions of pristine peatlands, and of degraded logged-over forests and old cropland.